Gambaran Tingkat Pengetahuan, Sikap, Perilaku, dan Dukungan Keluarga pada Penderita Hipertensi di Desa Mayangrejo Kabupaten Bojonegoro pada Tahun 2022 - Muhammad Dzaky Rizqi Muharram; Leo Soedharmadji (Media Gizi Kesmas, 2023)
Background: Hypertension often shows no complaints, but it will get complications from hypertension, such as heart and kidney risks. The prevalence of hypertension in Indonesia in 2018 was 8.4%. Non-communicable diseases (PTM) such as heart disease, stroke, cancer and other chronic diseases are the number one cause of death in Kabupaten Bojonegoro, East Java. Objectives: The purpose of this study was to find out the description of knowledge, attitudes, behaviour, and family support for hypertension sufferers in Desa Mayangrejo, Kabupaten Bojonegoro Methods: This research is a quantitative analytic survey with a cross-sectional design. The research subjects were 65 people with hypertension in Desa Mayangrejo, Kabupaten  Bojonegoro. Results: From the four aspects of the questionnaire, namely knowledge, attitudes, behaviour, and family support, it shows that hypertension sufferers in Desa Mayangrejo are in the very good category of 79.8%.. Conclusions: From the four aspects of the questionnaire, namely knowledge, attitudes, behaviour, and family support, it shows that hypertension sufferers in Desa Mayangrejo are in the very good category of 79.8%.